Hubungan Konsumsi Fast Food dan Screen Time Dengan Kejadian Gizi Lebih Siswa SMP Negeri 56 Palembang - Ardianty, Septi (jurnal kesehatan terapan sains dan teknologi, 2025)
Background: Overnutrition is one of the nutritional problems in Indonesia that is currently often found, especially in adolescents, caused by fast food consumption patterns and low physical activity (screen time) Objective: To determine the relationship between fast food consumption and screen time and the incidence of more nutrition among SMP Negeri 56 Palembang students. Method: This study is analytical descriptive research with a case-control design. The population in this study is students with more nutritional criteria, and sampling is carried out by the random sampling method, which is 62 students. Results: The statistical analysis results were obtained from two treatments, namely case and control, in the case of respondents with a high screen time of 71% and in the control case with a high sereen time of 87 1%. The analysis results on fast food consumption are often found in cases of 83.9% and in control cases classified as rare, which is 67.7%. The screen-time statistical test results obtained a p-value of 0.212> 0.05, meaning no relationship exists. The results of the statistical test of fast food consumption with more nutritional events obtained a p-value of 0.000 (≤0.05), meaning a significant relationship exists. Conclusion: There was no relationship between screen time and nutritional status with a p-value of 0.212 0.05, and there was a relationship between fast food and nutritional status with a p-value of 0.000 ≤0.05.